2017
DOI: 10.18488/journal.aefr.2017.712.1303.1316
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Cash Conversion Cycle: Evidence from Listed Companies in Sri Lanka

Abstract: The purpose of this study is to examine the impact of corporate governance on cash conversion cycle of Sri Lankan listed companies. This study adopted a co-relational research design. A sample of 90 Sri Lankan companies listed on the Colombo Stock Exchange for a period of five years (from 2011/12-2015/16) was used. The findings show that large number of directors and independent directors on the board and more number of meetings in a year shorten the cash conversion cycle (CCC) of Sri Lankan listed companies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Most empirical studies support higher dividend payouts as board size increases (Xie et al, 2003;Abdelsalam et al, 2008;Soliman, 2013;Roy, 2015;Benjamin and Zain, 2015;Mehdi et al, 2017;Juhmani, 2020;Suwaidan and Khalaf, 2020), while a minority find a negative relation (Khan, 2006;Roy, 2015). Further studies find no such relation between dividend payout and board size (Cheng, 2008;Ajanthan, 2013). From an agency theory perspective, smaller boards may produce greater agency costs and thus require higher dividend payouts for investors.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Most empirical studies support higher dividend payouts as board size increases (Xie et al, 2003;Abdelsalam et al, 2008;Soliman, 2013;Roy, 2015;Benjamin and Zain, 2015;Mehdi et al, 2017;Juhmani, 2020;Suwaidan and Khalaf, 2020), while a minority find a negative relation (Khan, 2006;Roy, 2015). Further studies find no such relation between dividend payout and board size (Cheng, 2008;Ajanthan, 2013). From an agency theory perspective, smaller boards may produce greater agency costs and thus require higher dividend payouts for investors.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Corporate governance has emerged as a significant determinant of dividend payout ratio. The decision with regard to dividend payout policy is often made by companies' management and can be influenced by its board of directors (Abdullah, Ahmad, & Roslan, 2012;Ajanthan & Kumara, 2017). The board of directors has fiduciary powers to make decisions with regard to how to finance the company operations and expansion, how to make an investment for the company, and distribute dividends to shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another study that has been conducted on Chinese listed firms from 2001-2007 showed a significant positive association between board size and cash dividend payments (Litai et al, 2011). On the contrary, other study have shown insignificant association between board size and dividends that was held on a sample of 17 companies listed on Colombo Stock Exchange during the period from 2008-2012 (Ajanthan, 2013). However, another study that has been done on Malaysian firms has divulged an insignificant and negative impact of board size and dividends (Bolbol, 2012).…”
Section: Hypotheses Development: 221 Board Size and Dividends Decisionmentioning
confidence: 95%
“…Moreover, another study that has been conducted on 237 companies from four Gulf Cooperation Council(GCC) countries: Bahrain, Oman, Saudi Arabia and the United Arab Emirates, which covered a period of 13 years from 3003-3015, showed that board independence has a moderating role on the association between dividends policy and agency costs (Hamdan, 2018). On the contrary, in a study among hotels and restaurant firms in Siri Lanka revealed insignificant relationship between board independence and dividends payout (Ajanthan, 2013). This result has been confirmed by another study, which showed as well insignificant effect of board independence on firm dividends ratio (Mansourinia et al, 2013).…”
Section: Board Independence and Dividends Decisionmentioning
confidence: 99%